20 Collaborative and interprofessional simulation training to promote integrated delivery of healthcare. (17th November 2016) - Vishwas, A; Attoe, C; Fernando, A
Abstract : Background: The need for more integrated services has become a necessity with an increase in the number of people with comorbid mental and physical health issues. 'No Health without Mental Health' (2009) highlighted the importance of recognising the link between physical and mental health and called for better services. The 2012 Kings Fund report outlines significantly poorer health outcomes and reduced quality of life in patients with comorbid physical and mental illness. In order to meet these challenges, it is imperative for healthcare professionals from physical and mental health settings to train together for better understanding and delivery of integrated care. With this in mind we made a number of changes to our existing course – Simulation Workshop at Mental Physical Interface (SWAMPI). A number of key issues were included as part of training such as Physical health CQUIN, Dementia CQUIN. We evaluated the changes to the training by assessing knowledge and confidence of course content and readiness for interprofessional learning as an indicator of interprofessional collaboration. Methods: This one day inter-professional training includes six simulated scenarios focussing on patients presenting with mental and physical comorbities. Pre and post questionnaires were administered to assess knowledge and confidence, while the Readiness for Interprofessional Learning Scale (RIPLS) assessed interprofessional attitudes. Findings: Pilot data has been collected from 15 participants (from 8 professional groups) who attended courses on 2 days. The quantitative analysis showed increases in knowledge and confidence and will be compared to previous courses and data when further data has been collected. RIPLS shows a high level of initial positive attitudes towards interprofessional learning, as well as an increase following the course. We hope in future to measure the impact of this training on clinical practice directly.